Migration of Phthalates From Polyethylene Terephthalate Bottles into Beverages: A Health Policy Brief - Tooraj Massahi; Amir Kiani; Ali Almasi; Jalil Jaafari; Nazir Fattahi; Kiomars Sharafi (Caspian Journal of Health Research)
Background: Phthalate compounds are among the harmful compounds that, under certain conditions, can migrate from the inner wall of polyethylene terephthalate (PET) bottles into the beverage in which they are contained. Objectives: This policy brief aims to discuss and investigate the factors influencing the release of phthalates from PET bottles into beverages. Methods: Following a narrative review approach, scientific studies and reports were sourced from reputable national and international databases. Key findings were analyzed to identify the most critical factors affecting phthalate migration. Results: The primary parameters influencing the migration of phthalates include the concentration of phthalates in bottle production, storage temperature, exposure to sunlight, duration of storage, and the reuse of bottles. Conclusion: This study highlights modifiable factors that impact the migration of phthalates from PET bottles. Health authorities should educate the public and beverage vendors to implement safe storage and usage practices, as outlined in this health policy brief.